2007
DOI: 10.1016/j.ceca.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Calcium mobilization via type III inositol 1,4,5-trisphosphate receptors is not altered by PKA-mediated phosphorylation of serines 916, 934, and 1832

Abstract: Several studies have shown that PKA-mediated phosphorylation of IP 3 R1 at serines S 1588 and S 1755 enhances the receptor's ability to mobilize Ca 2+ . In contrast, much less is known about whether Ca 2+ mobilization via IP 3 R2 and IP 3 R3 is regulated by PKA. We report here that IP 3 R2 is only very weakly phosphorylated in response to PKA activation and is probably not a physiological substrate for this kinase. IP 3 R3, however, is known to be phosphorylated by PKA at three sites (S 916 , S 934 and S 1832 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Previous studies have shown that exogenous IP 3 Rs are expressed at high levels in HEK 293T cells, such that the contribution of endogenous IP 3 Rs to biochemical measurements (e.g. IP 3 R phosphorylation) is negligible or undetectable (31). Immunoprecipitation of IP 3 R1 and IP 3 R2 recovered a considerable amount of 3F-Bok (Fig.…”
Section: Bok Associates With Ipmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that exogenous IP 3 Rs are expressed at high levels in HEK 293T cells, such that the contribution of endogenous IP 3 Rs to biochemical measurements (e.g. IP 3 R phosphorylation) is negligible or undetectable (31). Immunoprecipitation of IP 3 R1 and IP 3 R2 recovered a considerable amount of 3F-Bok (Fig.…”
Section: Bok Associates With Ipmentioning
confidence: 99%
“…4C). Vectors encoding IP 3 R1-3 have been described (31). The authenticity of all cDNAs was confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Establishing the PKA phosphorylation site(s) and subsequently performing mutagenesis of the putative sites in InsP 3 R2 are required to definitively rule out these and other possible mechanisms for the increased Ca 2ϩ signal. Although PKA has been shown to phosphorylate InsP 3 R2 in a number of studies by independent groups (21,26,28), the site(s) of phosphorylation are not known. Experiments were performed following transient overexpression of InsP 3 R2 in COS-7 cells.…”
Section: Activation Of Pka Enhances Camentioning
confidence: 99%
“…Pharmacological studies have shown that the calcium waves themselves involve an inositol-trisphosphate receptor (IP 3 R) pathway (Filosa et al, 2004), although the exact subtype of IP 3 Rs has not yet been determined (Yamamoto-Hino et al, 1995;Sharp et al, 1999;Holtzclaw et al, 2002, Cotrina andNedergaard, 2005). Although the three IP 3 R subtypes have similar channel properties, calcium release from the various subtypes can be differentially modulated by calcium, ATP, and phosphorylation (Foskett et al, 2007;Soulsby and Wojcikiewicz, 2007), thus modulating the resultant calcium wave.…”
mentioning
confidence: 97%